Radar talks. - Roumeliotis, Rachel (O'Reilly Media, Inc., 2022)
In this edition of Radar Talks, O'Reilly VP of content strategy Rachel Roumeliotis explores the state of AI adoption in 2022. See how your company compares with your peers in the research, adoption, and deployment of AI. You'll get a glimpse into the tools that AI experts are using, how they're using them, where they're hitting bottlenecks, and more. Recorded on July 11, 2022. See the original event page for resources for further learning or watch recordings of other past events. The O'Reilly Radar Talks series brings you expert opinions on emerging topics through hour-long interactive events. In conversation with some of the industry's top minds, you'll look at the early signals indicating significant trends and new technologies that will shape the future--and discover how to begin forging these technologies now. Share your own predictions and ask your questions while gaining insight into our experts' unique outlooks for the future.